Quantitative Genetic Variation in, and Environmental Effects on, Pathogen Resistance and Temperature-Dependent Disease Severity in a Wild Trout - Debes PV; Gross R; Vasemägi A (UNIV CHICAGO PRESS, 2025)
Health after pathogen contact varies among individuals because of differences in pathogen load (which is limited by resistance) and disease severity in response to pathogen load (which is limited by tolerance). To understand pathogen-induced host evolution, it is critical to know not only the relative contributions of nongenetic and genetic variation to resistance and tolerance but also how they change environmentally. We quantified nongenetic and genetic variation in parasite load and the associated temperature-dependent disease among trout siblings from two rivers. We detected a genetic variance for parasite load 6.6 times as large in the colder river. By contrast, genetic variance for disease traits tended to be larger in the warmer river, where the disease was manifested more severely. The relationships between disease severity and pathogen load (tolerance) exhibited plateaus at low pathogen load and stronger steepening slopes at high pathogen load in the warmer river. Our study demonstrates the environmental influence on disease severity, nongenetic and genetic variance for health-damage-limiting host abilities, and the shape of tolerance curves. Environmental variability is predicted to govern the presence and intensity of selection, change the relative contributions of nongenetic and genetic variance, and therefore hamper evolution toward more resistant and tolerant hosts.